Policy instrument mixes for operating modular technology within hybrid water systems. Issue 105 (March 2020) - Pakizer, Katrin; Fischer, Manuel; Lieberherr, Eva
Highlights: Policy instrument mixes are key for the successful operation of modular water technology within hybrid water systems. Multiple policy instrument configurations exist, showing that there is no silver bullet for operating modular technology. Regulatory instruments are relevant for operating modular technology within hybrid water systems, but not omnipresent. Participation and user responsibility support the operation of modular technology within hybrid systems by engaging users. Information dissemination is important in the context of modular technology, linking substantive and procedural instruments. Abstract: Water systems are experiencing dynamic societal demands and extreme environmental changes. The integration of modular water systems into existing centralized infrastructures, creating hybrid systems, could mitigate these challenges by enabling more resilient water management. However, the existence of technological alternatives has not changed the continuous reliance on centralized water infrastructure. Supportive policy instruments are key to foster the operation of modular technology within hybrid water systems. This article focuses on the role of substantive and procedural policy instruments for the successful operation of modular water systems within a hybrid water infrastructure. Based on Qualitative Comparative Analysis (QCA), we can confirm the claim in the literature that relying on regulatory instruments is relevant for operating modular technology within hybrid systems. However, we also find combinations of policy instruments where regulatory instruments do not matter. Furthermore, we find that procedural instruments emphasizing stakeholder participation interplay with different substantive policy instruments to support the successful operation of modular systems.